The Nature of Islamic Banking and Solvency Stress Testing : Conceptual Considerations - Jobst, Andreas A. (IMF Working Papers; Working Paper ;, 2020)
This paper provides a conceptual overview of key aspects of the design and implementation of solvency stress testing of Islamic banks. Based on existing regulatory standards and prudential practice, the paper explains how Islamic finance principles and their impact on various risk drivers affect the capital assessment of asset-oriented financial intermediation under stress. The formal specification of these risk factors helps operationalize and integrate the stress testing of Islamic banks within established frameworks for financial stability analysis.